Upper limb strength and performance deficits after glenohumeral joint stabilization surgery in contact and collision athletes - Fanning, E.; Daniels, K.; Cools, A.; Mullett, H.; Delaney, R.; McFadden, C.; Falvey, E. (Medicine & Science in Sports & Exercise, 2024)
Purpose The primary aim was to identify and quantify differences in interlimb asymmetry magnitudes across a battery of upper extremity strength and performance tests at 4 and 6 months after glenohumeral joint stabilization surgery shoulder stabilization in contact and collision athletes compared with an un-injured group. A secondary aim was to investigate if identified asymmetry magnitudes changed from 4 to 6 months after glenohumeral joint stabilization surgery. The third aim was to explore associations within the different performance and strength variables.